Chronic obstructive pulmonary disease and heart rate variability: a literature update - Roque, Adriano L.; Valenti, Vitor Engrácia [UNESP]; Massetti, Thais; Silva, Talita Dias da; Monteiro, Carlos Bandeira; Oliveira, Fernando R.; Almeida Júnior, Álvaro Dantas de; Lacerda, Sheylla Nadjane; Pinasco, Gustavo Carreiro; Nascimento, Viviane Gabriela; Granja Filho, Luiz Gonzaga; Abreu, Luiz Carlos de; et al. (My University, 2014)
Background: The literature indicates that chronic obstructive pulmonary disease (COPD) affects cardiac autonomic control. In this study, we conducted a literature review in order to investigate the heart rate variability (HRV) in COPD subjects. Methods: A search was performed in Medline database, using the link between the keywords: “autonomic nervous system”, “cardiovascular system”, “COPD” and “heart rate variability”. Results: The search resulted in a total of 40 references. Amongst these references, the first exclusion resulted in the barring of 29 titles and abstracts, which were not clearly related to the purpose of review. This resulted in a total of 11 articles that were then read and utilized in the review. The selected studies indicated that there is significant reduction of HRV in patients with COPD, characterized by reduction of indices that assess parasympathetic activity in addition to dealing with the global autonomic modulation. We also established that supervised exercise can reduce these harmful effects in COPD patients. Also, it was reported that the use of non-invasive ventilation in these patients may contribute to the improvement of respiratory symptoms, with no impairing, and may even induce positive responses in cardiac autonomic regulation. Conclusion: The studies indicate a need for further investigations to guide future therapies to improve the treatment of cardiovascular system in the respiratory diseases.